توزع القاعيات الحيوانية في المصاطب الفيرميتيدية Vermetid Platforms في الشاطئ السوري - عمار ازدهار (Latakia University Journal -Biological Sciences Series, 2019)
هذا البحث هو جزء من دراسة متكاملة أجريت للمرة الأولى على هذه التكوينات الهامة والحساسة في الشاطئ السوري واللبناني خلال الفترة 2006 - 2004 هدفت إلى دراسة تنوع وتوزع الكائنات الحيوانية والنباتية التابعة لمجموعات تصنيفية مختلفة في هذه المصاطب بالارتباط مع خصائصها الجيولوجية والبيئية. تمت دراسة المجتمعات القاعية المرافقة للمصاطب الفيرميتيدية في ثلاث مصاطب من الشاطئ السوري هي بانياس وجبلة والبسيط متضمنة تركيبها النوعي وتوزعها المناطقي. بلغ العدد الكلي للقاعيات الحيوانية في مناطق البحث الثلاثة (96) نوعاً وجنساً تنتمي إلى 10 وحدات تصنيفية. سجل وجود العدد الأكبر من الأنواع في مصطبة جبلة (65) نوعاً، تليها مصطبة البسيط (61) نوعاً، ثم بانياس (31) نوعاً. تلقي نتائج هذه الدراسة الضوء على أهمية المصاطب الفيرميتيدية في الإبقاء على التنوع الحيوي للقاعيات الحيوانية وتؤكد الحاجة إلى حمايتها وإدارتها بشكل سليم. This research is a part of an integrated study which has been carried for the first time of important and sensitive constructions of Syrian and Lebanese shores over the period 2004-2006. The purpose of the research is to study the diversity and distribution of fauna and flora in these platforms in correlation with their geological and ecological characteristics. Benthic communities associated with vermetid platforms were investigated in three selected platforms of the Syrian shore (Banias Jableh and Albassit) evaluating species composition and zonation A total of 96 species and genus of Zoobenthos belonging to 10 taxa were recorded over the three areas investigated. The highest number of species were recorded in Jableh platform (65) species, Albassit’s comes next with (61) species and Banas’s (31) species. The results of this study highlight the importance of Vermetid Platforms in sustaining the biodiversity of zoobenthos and emphasize the need for their protection and careful management.